Addressing cost and time barriers in chronic disease management through telemedicine: an exploratory research in select low- and middle-income countries. (December 2019) - Sayani, Saleem; Muzammil, Momina; Saleh, Karima; Muqeet, Abdul; Zaidi, Fabiha; Shaikh, Tehniat
Background: Despite evidence supporting telehealth provision in developed countries, there is limited evidence regarding its economic benefits for patients living in areas where access and cost present major barriers to health care, particularly in low- and middle-income countries (LMICs). This study explores the economic benefits of telemedicine for patients, in terms of cost and times savings, and its potential role in improving chronic disease outcomes. Methods: This retrospective cross-sectional study compared telemedicine services with hypothetical in-person consultations, with a focus on patient travel time and travel cost savings. A database containing teleconsultation visits ( N = 25, 182) conducted at health facilities in remote regions of Afghanistan, Pakistan, Tajikistan, and the Kyrgyz Republic, was analyzed. A two-sample homoscedastic t test was used to determine differences between the two groups. A one-way sensitivity analysis was also conducted, presuming in-person teleconsultations at 90%, 75%, and 50%. Results: The study extracted data from 25, 182 teleconsultation visits (12, 814 males; 12, 368 females). The cumulative patient savings through the program amounted to USD 9, 175, 132, and 1, 876, 146 h, or 213.1 years. A significant difference was seen between the two groups in terms of mean time savings ( p -value <0.05), and a nearly significant difference was observed in terms of mean cost savings ( p -value = 0.05). Conclusions: This study suggests that considerable economic benefits imparted to patients in low-resource settings of LMICs via accessing telemedicine. Telemedicine has great potential to improve chronic disease outcomes in low-resource areas by reducing socioeconomic barriers related to cost and access, and increasing uptake of services, thereby enabling early intervention and long-term management.